1999
DOI: 10.1038/sj.gt.3300870
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of variant-type of human α-fetoprotein promoter in gene therapy targeting for hepatocellular carcinoma

Abstract: We previously reported that the retroviral vector intermediate AFP-producing cells (PLC/PRF/5). By the (LNAFW0.3TK) expressing the herpes simplex thymidine reporter gene transfection assay, the activity of the variantkinase (HSVtk) gene under the control of the 0.3 kb human type of the promoter was much higher than that of the wild-␣-fetoprotein (AFP) promoter provided the ganciclovir type of the promoter in both HuH-7 and huH-1/cl.2 cells. (GCV)-mediated cytotoxicity in the high AFP-producing Consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Critically, only small amounts of E1a are required for viral replication and so specific but (relatively) weak eukaryotic promoters are not a drawback to the functional efficiency of such CRAd vectors. [Hallenbeck et al, 1999] [Ishikawa et al, 1999] [Kanai, 2001] carcinoembryonic antigen (CEA) CEA-expressing tumours [Brand et al, 1998] [Cao et al, 2001] [Qiao et al, 2002] erbB2 ERBB2-expressing tumours [Vassaux et al, 1999] mucin-1 (muc1) MUC1 (DF3)-expressing tumours [Stackhouse et al, 1999] [ Tai et al, 1999] L-plastin (LP-P) Epithelial-derived tumours [Chung et al, 1999] α-lactalbumin (ALA), Breast midkine (MK) Pancreatic [Yoshida et al, 2002] cyclooxygenase-2 (COX-2) Gastrointestinal et al, 2001] probasin (ARR2PB) Prostate Rubinchik et al, 2001] tyrosinase promoter Melanoma [Park et al, 1999] hypoxic response elements (HRE) Not tissue-specific [Dachs et al, 2000;Ruan H, 2001] hTERT Not tissue-specific [Gu et al, 2000;Koga et al, 2000;Lin et al, 2002;Majumdar et al, 2001] flt-1, flk1/KDR, E-selectin, endoglin, ICAM-2, preproendothelin 1 (PPE-1) [Southgate et al, 2000] osteocalcin 2 Osteosarcoma [Barnett et al, 2002] ABBREVIATIONS: PSA/PMSA, prostate-specific membrane antigen; hTERT, human telomerase reverse transcr…”
Section: Promoters For Cancer Gene Therapymentioning
confidence: 99%
“…Critically, only small amounts of E1a are required for viral replication and so specific but (relatively) weak eukaryotic promoters are not a drawback to the functional efficiency of such CRAd vectors. [Hallenbeck et al, 1999] [Ishikawa et al, 1999] [Kanai, 2001] carcinoembryonic antigen (CEA) CEA-expressing tumours [Brand et al, 1998] [Cao et al, 2001] [Qiao et al, 2002] erbB2 ERBB2-expressing tumours [Vassaux et al, 1999] mucin-1 (muc1) MUC1 (DF3)-expressing tumours [Stackhouse et al, 1999] [ Tai et al, 1999] L-plastin (LP-P) Epithelial-derived tumours [Chung et al, 1999] α-lactalbumin (ALA), Breast midkine (MK) Pancreatic [Yoshida et al, 2002] cyclooxygenase-2 (COX-2) Gastrointestinal et al, 2001] probasin (ARR2PB) Prostate Rubinchik et al, 2001] tyrosinase promoter Melanoma [Park et al, 1999] hypoxic response elements (HRE) Not tissue-specific [Dachs et al, 2000;Ruan H, 2001] hTERT Not tissue-specific [Gu et al, 2000;Koga et al, 2000;Lin et al, 2002;Majumdar et al, 2001] flt-1, flk1/KDR, E-selectin, endoglin, ICAM-2, preproendothelin 1 (PPE-1) [Southgate et al, 2000] osteocalcin 2 Osteosarcoma [Barnett et al, 2002] ABBREVIATIONS: PSA/PMSA, prostate-specific membrane antigen; hTERT, human telomerase reverse transcr…”
Section: Promoters For Cancer Gene Therapymentioning
confidence: 99%
“…Introduction of the respective reporter genes into HCC cell lines revealed that transcriptional activity of the 2.3-or 0.6-kb MK fragment was greater than that of the SV40 or the AFP promoter (Po0.001, Figure 2). Since HuH-7 and PLC/PRF/5 cells are AFPhigh and AFP-intermediate producers, respectively (Niwa et al, 1996;Ishikawa et al, 1999), the transcriptional activity of the AFP promoter was greater in HuH-7 than in PLC/PRF/5 cells. Addition of AFP enhancer augmented the AFP promoter-mediated transcriptional activation particularly in HuH-7 cells (Po0.001).…”
Section: Transcriptional Activity Of Mk and Afp Promotermentioning
confidence: 95%
“…Linkage of 0.2-kb AFP promoter and 0.9-kb AFP distal enhancer gave the maximal transcription of a fused reporter gene (Nakabayashi et al, 1991). We thereby examined the transcriptional activity of four kinds of reporter constructs (MK2.3-luc, MK0.6-luc, AFP0.2-luc and AFPEn0.2-luc) in AFP-producing (HuH-7 and PLC/PRF/5) and -nonproducing (HLE and HLF) HCC cell lines (Niwa et al, 1996;Ishikawa et al, 1999), and in non-HCC cell lines (MCF-7 and AsPC-1), which were positive for MK expression (Miyauchi et al, 2001). Introduction of the respective reporter genes into HCC cell lines revealed that transcriptional activity of the 2.3-or 0.6-kb MK fragment was greater than that of the SV40 or the AFP promoter (Po0.001, Figure 2).…”
Section: Transcriptional Activity Of Mk and Afp Promotermentioning
confidence: 99%
“…For this reason, several enhancers have been inserted into the upstream of the promoter in order to upgrade its activity [32][33][34][35] . In our study, the original enhancer in pshuttle was reserved, which might contribute to the satisfactory transcription of the downstream gene using the 0.3 kb promoter.…”
Section: Discussionmentioning
confidence: 99%